Safewards: the empirical basis of the model and a critical appraisal. Issue 4 (24th January 2014) - Bowers, L.; Alexander, J.; Bilgin, H.; Botha, M.; Dack, C.; James, K.; Jarrett, M.; Jeffery, D.; Nijman, H.; Owiti, J. A.; Papadopoulos, C.; Ross, J.; et al.
<x xml:space="preserve">Abstract</x> Accessible summary In the previous paper we described a model explaining differences in rates of conflict and containment between wards, grouping causal factors into six domains: the staff team, the physical environment, outside hospital, the patient community, patient characteristics and the regulatory framework. This paper reviews and evaluates the evidence for the model from previously published research. The model is supported, but the evidence is not very strong. More research using more rigorous methods is required in order to confirm or improve this model. Abstract In a previous paper, we described a proposed model explaining differences in rates of conflict (aggression, absconding, self‐harm, etc.) and containment (seclusion, special observation, manual restraint, etc.). The Safewards Model identified six originating domains as sources of conflict and containment: the patient community, patient characteristics, the regulatory framework, the staff team, the physical environment, and outside hospital. In this paper, we assemble the evidence underpinning the inclusion of these six domains, drawing upon a wide ranging review of the literature across all conflict and containment items; our own programme of research; and reasoned thinking. There is good evidence that the six domains are important in conflict and containment generation. Specific claims about single items within those domains are more difficult to support with convincing evidence, although the weight of evidence does vary between items and between different types of conflict behaviour or containment method. The Safewards Model is supported by the evidence, but that evidence is not particularly strong. There is a dearth of rigorous outcome studies and trials in this area, and an excess of descriptive studies. The model allows the generation of a number of different interventions in order to reduce rates of conflict and containment, and properly conducted trials are now needed to test its validity.